Social Innovation: The Era of Searching and Refining - Loudín, Jiří (Teorie vědy / Theory of Science, 2015)
This essay reviews and analyzes the development of the concept of social innovation. In the wake of increasing societal demand, an initially partial and undertheorized category has developed into a general concept, which covers a broad field of immaterial innovation and presents itself as a normative and intentional practice. Among various ideological orientations, the study identifies a mainstream approach with its open attitude towards values, emancipatory-mobilizing stance and a socially- and market-responsible approach. At an epistemological level, theorists of social innovation typically embrace practical experiments, pragmatism, complexity theory and the principles of transdiciplinarity.